FACTUAL ACTION AS ADMINISTRATIVE DISPUTES (PROHIBITION OF MISLEADING LAWSUIT BETWEEN THE ADMINISTRATIVE DECISION AND THE FACTUAL ACTION) - David Pasaribu; Istislam; Sudarsono (CV. RADJA PUBLIKA, 2025)
This article attempts to comprehend the ideal concept of factual action and analyzes factual action as an object of dispute in the Administrative Court (